Suits. Season nine [videorecording (DVD)] : the final season - Macht, Gabriel, 1972-; Hoffman, Rick, 1970-; Rafferty, Sarah; Hill, Dulé; Schull, Amanda, 1978-; Heigl, Katherine (Universal Pictures Home Entertainment, 2019)
Harvey and Samantha fight to keep Zane's name on the wall. Alex warns Louis of the consequences. Faye decides to take action against Harvey and Donna's relationship. Harvey looks to impress Donna's father. As the firm faces potential destruction, the partners must go all-in to save it.